2017
DOI: 10.1038/s41598-017-10087-6
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Activation of PERK-Nrf2 oncogenic signaling promotes Mdm2-mediated Rb degradation in persistently infected HCV culture

Abstract: The mechanism of how chronic hepatitis C virus (HCV) infection leads to such a high rate of hepatocellular carcinoma (HCC) is unknown. We found that the PERK axis of endoplasmic reticulum (ER) stress elicited prominent nuclear translocation of Nrf2 in 100% of HCV infected hepatocytes. The sustained nuclear translocation of Nrf2 in chronically infected culture induces Mdm2-mediated retinoblastoma protein (Rb) degradation. Silencing PERK and Nrf2 restored Mdm2-mediated Rb degradation, suggesting that sustained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 72 publications
2
34
0
Order By: Relevance
“…136 The subsequent publication showed that excessive ER stress induces MDM2-mediated Rb degradation. 137 All these results are consistent with human studies that show more than 70% of HCC cases having alterations in the p53-Rb pathway that leads to mitosis, cell cycle progression, and genomic instability.…”
Section: Telomerase Reverse Transcriptase (Tert)supporting
confidence: 90%
See 1 more Smart Citation
“…136 The subsequent publication showed that excessive ER stress induces MDM2-mediated Rb degradation. 137 All these results are consistent with human studies that show more than 70% of HCC cases having alterations in the p53-Rb pathway that leads to mitosis, cell cycle progression, and genomic instability.…”
Section: Telomerase Reverse Transcriptase (Tert)supporting
confidence: 90%
“…In addition, our laboratory illustrated that virus-associated ER stress and tumor suppressor loss (p53 and Rb, miR-122 levels) were restored more by IFN-induced HCV clearance than DAAs in cell culture models. 136,137,206 Based on these data, we propose that understanding the impact of viral cure on the resolution of direct hepatic parenchymal injuries and indirect immune restoration may explain as to why specific individuals remain at risk of HCC occurrence and recurrence.…”
Section: Reversal Of Direct Mechanisms After Daas Treatmentmentioning
confidence: 99%
“…CHIKV infection in HeLa cells leads to activation of the PERK/eIF2␣ branch of the UPR, the induction of autophagy and apoptosis, implying that PERK/ eIF2␣ pathway could play a role in CHIKV-induced apoptosis (26). Interestingly, sustained activation of PERK axis of ER-stress during chronic HCV infection activates the oncogenic Nrf2 signaling that promotes hepatocyte survival (39). Our data strongly indicate that JEV infection in vivo and in vitro induces PERK activation by promoting its dimerization, resulting in cell apoptosis via the PERK-ATF4-CHOP pathway (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of pancreatic ductal adenocarcinoma (PDAC), SQSTM1mediated activation of Nrf2 also results in the induction of the ubiquitin ligase MDM2, which further aggravates cancer progression by promoting degradation of p53 and inducing the Notch signaling pathway (Todoric et al, 2017). This Nrf2-dependent MDM2 activation may also be present in cells persistently infected with hepatitis C virus, where it results in degradation of retinoblastomaassociated protein (RB1) and development of HCC (Aydin et al, 2017). Besides, there are at least two other main signaling pathways affecting cancer development through SQSTM1, namely NF-κB and mTORC1 (Reina-Campos et al, 2018).…”
Section: Cancermentioning
confidence: 99%